2006
DOI: 10.1021/cg060045x
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Structure Agglomerates of Calcium Carbonate Crystals Formed on a Cation-Exchange Membrane

Abstract: Crystallization of calcium carbonate was carried out by using 1 M calcium chloride and 1 M sodium carbonate and a specially designed crystallizer equipped with a cation-exchange membrane. The crystallizer is a jacketed cylindrical glass tube that was divided into two compartments by a cation-exchange membrane and placed horizontally. Calcium carbonate crystals grew on the surface of the cation-exchange membrane in the sodium carbonate solution side and formed self-assembled tubular agglomerates vertically agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
2
21
0
2
Order By: Relevance
“…The tube grew longer with time. As reported in the previous paper, 11) the growing site of the tube is the bottom of tubes. It is reconfirmed by a fact that the bending part of the tube does not grow longer.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The tube grew longer with time. As reported in the previous paper, 11) the growing site of the tube is the bottom of tubes. It is reconfirmed by a fact that the bending part of the tube does not grow longer.…”
supporting
confidence: 60%
“…We have studied the role of membrane on the crystallization of calcium carbonate, 11) where 1 M sodium carbonate and 1 M calcium chloride solutions were separately placed in two compartments of the crystallizer that were divided by a cation-exchange membrane. Calcium ions permeated the membrane and reacted with carbonate ions in the sodium carbonate solution.…”
Section: Introductionmentioning
confidence: 99%
“…As references reported, smooth tube may be composed of vaterite. 15 Furthermore, it is found from Figure 1a that the tube has a cap on the top. The cap is hemispheric and is composed of small crystals with cubic and rectangle shapes.…”
Section: Resultsmentioning
confidence: 96%
“…Tubular structure agglomerates of calcium carbonate crystals were synthesised on a cation-exchange membrane with 1 mol•L -1 CaCl 2 and 1 mol•L -1 Na 2 CO 3 solutions by Takiguchi et al 15 In their experiment, crystallization of calcium carbonate was carried out by using 1 mol•L -1 calcium chloride and 1 mol•L -1 sodium carbonate and a specially designed crystallizer equipped with a cation-exchange membrane. Calcium carbonate crystals grew on the surface of the cation-exchange membrane in the sodium carbonate solution side and formed self-assembled tubular agglomerates vertically against the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
“…Literature on crystallization of CaCO 3 showed that the nature of the template used and temperature affected the morphology of crystallized CaCO 3 [1][2][3][4][5][6][7][8][9]. However, elucidation of the surface properties of the crystallized CaCO 3 crystals in terms of the location of the polymeric additive is additionally important for application purposes.…”
Section: Introductionmentioning
confidence: 99%